(untitled) (Kohesi: Jurnal Sains dan Teknologi, 2025)
This research examines the utilization of cloud computing as a disaster recovery (DR) and business continuity (BC) solution for the main information systems at Universitas Pamulang. The university’s dependence on digital systems increases vulnerability risks to disruptions that could potentially lead to data loss and service disruption. The objective of this research is to formulate a strategic model for implementing an effective cloud-based DR/BC, focusing on crucial systems such as the Academic Information System (SIAKAD) and Financial Information System. The research method uses an iterative approach, involving a repeating cycle of risk analysis, solution design, conceptual implementation, and simulated testing. This approach allows for gradual risk identification and mitigation, as well as adaptation to evolving needs. The implementation of cloud computing is expected to provide a scalable, flexible, and cost-effective recovery environment, ensuring rapid data and operational availability post-disaster. The results of this research will provide a practical framework for Universitas Pamulang to strengthen the resilience of its information systems, minimize downtime, and maintain the continuity of educational services amidst potential threats. Keywords: Cloud Computing,Disaster Recovery (DR), Kontinuitas Bisnis (BC), Information Systems, Universitas Pamulang Abstract Penelitian ini mengkaji pemanfaatan cloud computing sebagai solusi disaster recovery (DR) dan kontinuitas bisnis (BC) untuk sistem informasi utama di Universitas Pamulang. Ketergantungan perguruan tinggi terhadap sistem digital meningkatkan risiko kerentanan terhadap gangguan yang berpotensi menyebabkan kehilangan data dan disrupsi layanan. Tujuan penelitian ini adalah merumuskan model strategis untuk mengimplementasikan DR/BC berbasis cloud yang efektif, dengan fokus pada sistem krusial seperti Sistem Informasi Akademik (SIAKAD) dan Sistem Informasi Keuangan. Metode penelitian menggunakan pendekatan iteratif, melibatkan siklus berulang analisis risiko, perancangan solusi, implementasi konseptual, dan pengujian simulasi. Pendekatan ini memungkinkan identifikasi dan mitigasi risiko secara bertahap, serta adaptasi terhadap kebutuhan yang berkembang. Implementasi cloud computing diharapkan mampu menyediakan lingkungan pemulihan yang skalabel, fleksibel, dan hemat biaya, memastikan ketersediaan data dan operasional yang cepat pasca-bencana. Hasil penelitian ini akan memberikan kerangka kerja praktis bagi Universitas Pamulang untuk memperkuat ketahanan sistem informasinya, meminimalkan waktu henti, dan menjaga keberlangsungan layanan pendidikan di tengah ancaman potensial. Kata Kunci: Cloud Computing,Disaster Recovery (DR), Kontinuitas Bisnis (BC), Sistem Informasi, Universitas Pamulang